Improving aerial counts of Maasai livestock - King, J.M.; Sayers, A.R.; Chara, P.; Leeuw, P.N. de; Peacock, C.P. (Elsevier, 1985)
Describes use of low - level aeral census in counting livestock in Kenya's Maasailand Group Ranches, concentrating on survey designs & efforts made to improve reliability of population estimates, Compares efficiency & precision of aerial & ground counts.